Substitution of Manual Production Labor by Automation - Lee, Lai Samm (2017)
Automation has been increasingly practiced in various industry especially manufacturing sector where most of the manual repetitive and low skill jobs are replaced by technology innovation. However, automation substitution does not practically applied in every industry due to level of investment, limitations of technology development, agility in deploying sophisticated technology solutions in industrial environment and many more constraints. Based on literature reviews from researchers, industry clockspeed, integration of automation in global supply chain, automation in lean production and business process reengineering (BPR) has become the factors driving the pace of automation in industry (Mendelson and Pillai, 1999), (Wu L. et al. 2016), (Mrugalska,B. and Wyrwicka, M.K., 2017), (Aral S. et al., 2006). Therefore, the objective of this research is to identify the possibility of substituting production labor with automation in the labor populated manufacturing industries: automotive; textile, clothing and footwear; and E&E (electrical and electronic) industry. By collecting secondary data and categorized the production and employment rate between developed and developing country in each industry, the concept of automation replacing labors is identified by generating a hypothesis: when productivity increased and employment level decreased, substitution of manual labor by automation is occurred. Besides comparing data, practical introduction of automated production firm in each industry is discussed in this research. My findings indicate that automotive and E&E (electrical and electronic) industry are more susceptible to be substitute by artificial intelligence than clothing, textile and footwear industry. On the other hand, automation applications are less capable in replacing the needs of labor in developing country than developed country.